Heroism and paramedic practice: A constructivist metasynthesis of qualitative research - Rees, Nigel; Williams, Julia; Hogan, Chloe; Smyth, Lauren; Archer, Thomas (Frontiers in Psychology, 2022)
Abstract Objectives: We aimed to identify, appraise, and synthesise the qualitative literature to develop theory on heroism and paramedic practice. Hypothesis/research question: What does published literature tell us about heroism and paramedic practice? Setting: Paramedics and other healthcare workers (HCWs) faced an outpouring of public support for them early in the COVID-19 pandemic which brought into focus the relationship between them and society, where they are portrayed as heroes. Participants: We conducted a metasynthesis using Evolved Grounded Theory and procedural guidelines of Noblit and Hare to guide analysis. Preferred Reporting Items for Systematic Reviews and Meta-analysis Protocols (PRISMA-P) guidelines were also applied. Results: 151 papers were retrieved and eleven included in the final sample. Studies were moderate to very low quality, involving a wide range of methodologies and settings; none specifically explored heroism and paramedic practice. The following interrelated themes were constructed on heroism and paramedic practice: (a) Myth, Folk law, and storytelling in heroism and paramedic practice (b) The epic journey of heroism and paramedic practice (c) Heroes and Zeroes: The fluctuating Societal Value in heroism and paramedic practice (d) Politicisation, and objectification in Heroism and Paramedic practice. Conclusion: Paramedics have long been characterised as heroes, but this may not reflect their everyday experiences. Heroism in paramedic practice can provide scripts for prosocial action, inspiring others and leading to more social heroic actions. Paramedics may however be ambivalent to such heroism narratives, due to politicisation, and objectification in the media and society. This metasynthesis is only one of many possible constructions of heroism and paramedic practice and is the first point in making sense of and developing theory on heroism and paramedic practice.